2008
DOI: 10.1186/1471-2202-9-13
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of apoptosis in neuronal cells infected with Chlamydophila (Chlamydia) pneumoniae

Abstract: Background: Chlamydophila (Chlamydia) pneumoniae is an intracellular bacterium that has been identified within cells in areas of neuropathology found in Alzheimer disease (AD), including endothelia, glia, and neurons. Depending on the cell type of the host, infection by C. pneumoniae has been shown to influence apoptotic pathways in both pro-and anti-apoptotic fashions. We have hypothesized that persistent chlamydial infection of neurons may be an important mediator of the characteristic neuropathology observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…We further showed that astrocytes and microglia were host cells for the organism in the AD brain, and in recent studies we and others have identified neurons as host cells for the organism as well (Balin et al, 1998; Gérard et al, 2006; Appelt et al, 2008). …”
Section: Introductionsupporting
confidence: 69%
“…We further showed that astrocytes and microglia were host cells for the organism in the AD brain, and in recent studies we and others have identified neurons as host cells for the organism as well (Balin et al, 1998; Gérard et al, 2006; Appelt et al, 2008). …”
Section: Introductionsupporting
confidence: 69%
“…Listeria monocytogenes, Borrelia burgdorferi , Treponema pallidum and Mycobacterim leprae target neurons at the periphery in order to evade the host immune response and gain access to the relatively ‘immune‐privileged’ environment of the CNS. C. pneumoniae , similar to M. tuberculosis , establishes infection within the lung, disseminates and through phagocyte facilitation traverses the blood–brain barrier, where the bacteria are free to infect neurons 86 , 87 , 88 , 89 , 90 . It was recently demonstrated the association and subsequent internalisation of M. tuberculosis by murine and human‐derived neuronal cell lines and primary neurons in culture and in vivo.…”
Section: Glial and Neuronal Cellsmentioning
confidence: 99%
“…[35] The ability of the intracellular C. pneumoniae to enable the neuron to resist apoptosis and enter a chronic infective/inflammatory state has been more recently described. [36] The suggested consequence of this latency is an upregulation of amyloid production and processing. More recently, it has been demonstrated that the brains of Alzheimer's disease individuals carrying APOE4 have increased C. pneumoniae burden compared with non-APOE4 carriers.…”
Section: Chlamydophila Pneumoniaementioning
confidence: 99%